ACADEMY OUTDOORS: EXPANDING POSSIBILITIES (Fiep Bulletin - online, 2014)
Lack of physical activity is the biggest health problem of the 21st century. For both appear to academies outdoors with the proposal to promote an improved quality of life for all ages, through physical activity . Although this is the big "ideology" publications direct gyms outdoor practically for seniors. The objective of this article was to identify opportunities in a global view of the physical outdoor activities specifically air academies outdoors in the literature over the past 10 years. Methodologically systematic review of best international data sources was performed. We conclude that the proposals involve changing habits is a new environment for physical activity. Because of articles found in the readings of the last 10 years that physical activity outdoors and outdoor gyms promote longevity of interventions. Besides being more attractive to practitioners and provide the same benefits of the activities indoors. And the only obstacle is the cost, but spending on facilities compared to public health expenditures are insignificant without counting the number of beneficiaries that can take advantage of the space on schedule that suits you best .
Keywords: outdoor gym; physical activity; health.